The category of “death” in a text concept of M. Khvylovyy’s novels (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
Artistic thanatology becomes the new research field of contemporary literature. Thanatological motives of M. Khvylovyy’s creative concept left unattended by scientists, which is an obstacle to comprehension of the writer’s individual style.The article adherently shows a tragic motive of the world brutal restructuring, to the rules of which the person is not ready. The text selection caused by a distinct psychology of the characters, which is manifested through the constant “death”. Author puts characters in the same conditions: the loss of ideological illusions committed in frustration, a sense of superficial things in the “winners festival”, the constant environmental pressure. The main characters of stories exist in non-existent world of revolution, which is the “Dreamland” and the “country of explosions” at the same time. The central characters are endowed with “conflict” social status. In the early 20s they faced with frustration and depression due to the inability to find usability of their potential. The study focused on the important components of existential conflict between the desire for self-fulfillment and the lack of prospects. And then – psychological tension, depression, passionate looking into death.
Keywords: “conflict-” social status; existential contradiction